DNA repair at the gene level in trichothiodystrophy cells - Nathan , Sheila; Mayne, Lynne (Universiti Kebangsaan Malaysia, 2000)
Cells from trichothiodystrophy (TTD) group 3 patients are non-hypersensitive to uv irradiation. These cells perform normal genome repair of pyrimidine dimers but fail to excise 6-4 photoproducts and concomitantly, are unable to restore RNA synthesis levels following uv irradiation. This pointed to a defect in gene-specific repair and this study was undertaken to examine repair of dimers at the gene-level. The results indicated a defect in gene-specific repair of dimers at early times post-irradiation due to the inability of the cells to repair dimers from the transcribed strand of the active gene. These findings indicate that TTD group 3 cells are unable to remove DNA lesions preferentially and this might contribute to other inherent symptoms of these patients.